Physical and mechanical properties of fiberboard made from corn cob and coconut fiber with natural adhesives - Hasanah, Moraida; Marlina, Hilda Ayu; Zahar, Intan; Kadir, Abdul Azis (Politeknik Negeri Lhokseumawe, 2024)
Developing fiberboard from agro-industrial and natural waste has a significant impact on environmental practices. Fiberboards made from corncobs and coconut fiber have become a desirable by-product that can serve as a wood substitute. This research aims to analyze the physical and mechanical properties of fiberboard composites created from coconut husks and corn cobs, using natural adhesives like tapioca glue and citric acid. Corn cob particles and coconut fruit fibers were weighed in a 1:1 ratio. Tapioca glue or citric acid was then added in varying percentages: 10%, 14%, 18%, 22%, and 26% of the total mixture. This blend was poured into molds, spread evenly with a spatula, and pressed under 30 kg/cm² (426.7 psi). Subsequently, the samples were carefully removed for physical and mechanical testing. The findings of the study indicated that the different mass variations of corncobs and coconut fibers mixed with natural adhesives successfully produced fiber composites that met the Japanese Industrial Standards (JIS) A 5095:2003 for the